Hungarian Monitoring, 16 January 1989 . [Magyar rádiófigyelő], 1989. január 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Soviet journalists at the Washington HQ of Radio Liberty, Pravda reports - Moscow's opinion on the Vienna follow-up talks - Japanese paper on Western help for Hungarian and Poland - Reform debates at the Polish Central Committee - Afghan king prepares to return home - Will there be a churches law in the USSR? Domestic Affairs: - Károly Grósz confirms invitation to new American president, G. Bush - Not out of the question that Hungary will join UN refugees body - Péter Várkonyi arrives in Vienna for closing meeting of conference - Independent Lawyers' Forum representative on the Forum's bridging role between society and the authorities - International press conference on saving the Jurta Theater - On the destruction of the Regnum Marianum - Report on disillusioned miners from the Mecsek regionl - Documentary book on the Rajk trial published Economy: - TOT presidium sitting hears that 150-160 agricultural cooperatives are in danger, and not 60 - "Two-thirds of state farms struggle to make payments", was announced at farm managers' meeting Külpolitika: - Szovjet újságírók a SZABADSÁG RÁDIÓ washingtoni központjában - Tudósít a Pravda - Moszkvai vélemény a bécsi utótalálkozóról - Egy japán lap a Magyarországnak és Lengyelországnak nyújtandó nyugati segítségről - Reform viták a lengyel központi bizottságban - Az afgán király haza készül - Lesz-e egyházügyi törvény a SZU-ban? Belpolitika: - Grósz Károly megerősítette az új amerikai elnöknek, G. Bushnak szóló magyarországi meghívást - Nem kizárt, hogy Magyarország csatlakozik az ENSZ menekültügyi szervezetéhez - Várkonyi Péter Bécsbe érkezett a bécsi konferencia záró szakaszára - Független Jogász Fórum képviselője a Fórum híd-szerepéről a társadalom és a hatalom között - Nemzetközi sajtótájékoztató a Jurta Színház megmentéséről - A Regnum Marianum korabeli lebontásáról - Riport elkeseredett mecseki bányászokkal - Dokumentumkötet jelent meg a Rajk-perről Gazdaság: - Nem 60, hanem 150-160 tsz van veszélyben, állították a TOT elnökségi ülésén - Az állami gazdaságok kétharmada küzd fizetési nehézségekkel- közölték a gazdaságok vezetőinek értekezletén melyen részt vett Németh Miklós kormányfő is